Analisis Kualitas Internet Marketing Berbasis Aplikasi Android “Feuniskamarket” - Diana Ambarwati; Iing Sri Hardiningrum; Nur Hidayati (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2018)
This study aims to analyze the quality of Internet Marketing based on the Android application "FEUNISKAMarket". This quantitative study conducted descriptive approach using the help of questionnaires in accordance with the research variable indicators. The process of dissemination and data collection is given randomly, sampling accidental non random probability non sampling by giving a questionnaire to 25 students who posted their products in the Android application "FEUNISKAmarket" and were willing to fill out questionnaires in May and June 2018. The results of this study indicate that all the most respondents are female students with the age range between 20 to 30 years as users of the Android Internet Marketing application "FEUNISKAmarket" stated agree and simply agree with the quality statement of the android application that has fulfilled aesthetic elements, user convenience, multimedia techniques and content that are interesting to see. However, disagree with the statement that the android application is already known by many people. It is expected that respondents can help socialize this android application to many people and researchers can then expand the population and sample if you want to examine the same variables and objects.Penelitian ini bertujuan untuk menganalisis kualitas Internet Marketing berbasis aplikasi android “FEUNISKAMarket”. Penelitian kuantitatif ini melakukan pendekatan secara deskriptif dengan menggunakan bantuan angket/kuesioner sesuai dengan indikator variabel penelitian. Proses penyebaran dan pengumpulan data diberikan secara acak yaitu sampling accidental non random probability non sampling dengan memberikan angket pada 25 mahasiswa yang memposting produknya di aplikasi android “FEUNISKAmarket” dan bersedia mengisi kuesioner pada bulan Mei dan Juni 2018. Hasil penelitian ini menunjukkan bahwa seluruh responden terbanyak yaitu mahasiswa perempuan dengan rentang umur antara 20 s/d 30 tahun sebagai pengguna aplikasi android  Internet Marketing“FEUNISKAmarket” menyatakan  setuju dan cukup setuju dengan pernyataan kualitas aplikasi android sudah memenuhi unsur estetika, kemudahan pengguna,  teknik multimedia dan menu (konten) yang menarik untuk dilihat. Namun, tidak setuju dengan pernyataan bahwa aplikasi android sudah dikenal oleh banyak orang. Diharapkan responden dapat membantu mensosialisasikan aplikasi android ini pada banyak orang dan peneliti selanjutnya dapat memperluas populasi dan sampel jika ingin meneliti dengan variabel dan objek yang sama